Mechanisms of the gabapentinoids and α2δ‐1 calcium channel subunit in neuropathic pain. Issue 2 (27th February 2016) - Patel, Ryan; Dickenson, Anthony H.
Abstract: The gabapentinoid drugs gabapentin and pregabalin are key front‐line therapies for various neuropathies of peripheral and central origin. Originally designed as analogs of GABA, the gabapentinoids bind to the α 2 δ ‐1 and α 2 δ ‐2 auxiliary subunits of calcium channels, though only the former has been implicated in the development of neuropathy in animal models. Transgenic approaches also identify α 2 δ ‐1 as key in mediating the analgesic effects of gabapentinoids, however the precise molecular mechanisms remain unclear. Here we review the current understanding of the pathophysiological role of the α 2 δ ‐1 subunit, the mechanisms of analgesic action of gabapentinoid drugs and implications for efficacy in the clinic. Despite widespread use, the number needed to treat for gabapentin and pregabalin averages from 3 to 8 across neuropathies. The failure to treat large numbers of patients adequately necessitates a novel approach to treatment selection. Stratifying patients by sensory profiles may imply common underlying mechanisms, and a greater understanding of these mechanisms could lead to more direct targeting of gabapentinoids.